(untitled) (Research, Society and Development, 2022)
Handgrip strength (HGS) is considered a fundamental component in older adults’ muscle strength (MS) analysis. However, the evidence that shows its relationship with global MS is still inconclusive. The present study aimed to determine whether the relative handgrip strength (RHGS) is representative of the overall MS in the elderly. Thirty-nine older women participated in the present study (age 69.02 ± 6.16 years, height 1.55 ± 0.06 m, body mass index (BMI) 27.51 ± 4.10 kg /m², fat 38.80 ± 6, 28%). To measure the absolute MS of the upper and lower limb, participants underwent tests of 10 maximum repetitions in the bench press, seated close grip row, leg seated machine hamstring curl, leg seated extension curl, and horizontal leg press. 1 RM was also estimated. The absolute HGS was assessed using a hydraulic handgrip dynamometer. To calculate the RHGS, the highest reading was divided by BMI and entire arm muscle in kilograms measured by DXA. The same procedure was performed to calculate the relative MS from the upper and lower limbs. The RHGS results presented a moderate and significant correlation with the relative strength of hamstring curl, bench press, and seated close grip row; however, in the other exercises, there was no correlation. Therefore, although the RHGS has shown a moderate and significant correlation with the relative strength of the upper and lower limbs, caution is still recommended when stating that the RHGS is a representative variable of the overall muscle strength in older adults.